EVALUATING THE IMPACT OF QUALITY CONTROL MEASURES ON THE RELIABILITY OF BIOCHEMICAL ASSAYS IN CLINICAL LABORATORIES - Asma Nafe Thowaini Al-Shammari, Safanah Mohamed Ibrahim Al-Sghier, Salmah Mashhi Hamad Al-Dhfeeri, Hessah Khalid Al-Duraywish, Maali Jmaah Al-Anazy, Bodor Sabir Al-Anazy (Chelonian Research Foundation, 2022)
Quality control measures are essential for ensuring the reliability and accuracy of biochemical assays in clinical laboratories. This study aims to evaluate the impact of quality control measures on the reliability of biochemical assays in clinical laboratories in Saudi Arabia. A mixed-methods approach was employed, involving a survey of 150 laboratory technicians and semi-structured interviews with 15 laboratory managers. The survey assessed the implementation of quality control measures, the frequency of quality control testing, and the perceived impact on assay reliability using a 5-point Likert scale. The interviews explored the challenges and best practices in implementing quality control measures. The findings revealed a significant positive relationship between the frequency of quality control testing and perceived assay reliability (r=0.78, p<0.001). Laboratories that performed daily quality control testing reported higher assay reliability compared to those with weekly or monthly testing. The study highlights the importance of regular quality control testing and adherence to standardized protocols in ensuring the reliability of biochemical assays in clinical laboratories. Keywords: quality control, biochemical assays, clinical laboratories, assay reliability, Saudi Arabia